Method for producing particulate (oxy)hydroxide, and particulate (oxy)hydroxide
The controlled precipitation method for nickel and manganese hydroxides in lithium ion battery precursors addresses the issue of non-uniform particle sizes, resulting in high-density electrode materials with enhanced cycling stability and capacity.
Patent Information
- Application Number
- JP2024542157
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-06
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for producing precursors for lithium ion battery cathode materials result in non-uniform particle sizes and shapes, affecting the performance and lifespan of the batteries.
A method involving the controlled precipitation of nickel and cobalt or manganese hydroxides in stirred tank reactors with pH adjustment and solid-liquid separation, producing highly spherical precursors with a narrow particle size distribution.
The method yields precursors with a narrow particle size distribution and oriented primary particles, leading to high-density electrode active materials with improved cycling stability and capacity retention.
Smart Images

Figure 2025502315000002 
Figure 2025502315000003 
Figure 2025502315000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the preparation of particulate (oxy)hydroxides of TM, where TM represents a combination of nickel and at least one metal selected from Co and Mn, said method comprising the following steps: (a) providing an aqueous solution (α) containing a water-soluble salt of Ni, at least one metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta, an aqueous solution (β) containing an alkali metal hydroxide, and optionally an aqueous solution (γ) containing ammonia; (b) combining solution (α), solution (β), and, where applicable, solution (γ) in a continuous stirred tank reactor at a pH value in the range of 12.0 to 13.0 determined at 23° C. to produce solid particles of nickel-containing hydroxide, the solid particles being slurried; (c) transferring the slurry from step (b) to a batch stirred tank reactor where solution (α), solution (β), and, where applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0, determined at 23° C.; Including, Here, each stirred tank reactor(s) is equipped with a solid-liquid separation device, such as a clarifier or filtration device, in particular at least one candle filter, through which the mother liquor is removed from the stirred tank reactor(s). [Background technology]
[0002] Lithiated transition metal oxides are currently used as electrode active materials in lithium-ion batteries. Extensive research and development has been carried out over the past few years to improve properties such as charge density, specific energy, and other properties such as cycle life degradation and capacity loss that adversely affect the life or applicability of lithium-ion batteries. Further efforts are being made to improve the manufacturing methods.
[0003] In a typical process for the preparation of cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitation of the transition metal as a carbonate, oxide, or preferably as a hydroxide. This precursor is then mixed with a lithium source, such as, but not limited to, LiOH, Li2O, or Li2CO3, and calcined at high temperature. The lithium salt(s) can be used as hydrate(s) or in dehydrated form. Calcination or calcination, often also referred to as thermal or heat treatment of the precursor, is usually carried out at temperatures in the range of 600-1000°C. During the heat treatment, a solid-state reaction takes place to form the electrode active material. The heat treatment is carried out in the heated zone of an oven or kiln.
[0004] The characteristics of the precursor are reflected to some extent in the characteristics of each electrode active material, such as particle size distribution, the content of each transition metal, etc. Therefore, it is possible to affect the properties of the electrode active material by controlling the characteristics of the precursor. Summary of the Invention [Problem to be solved by the invention]
[0005] It is an object of the present invention to provide a method for producing highly spherical precursors with narrow particle size distribution. It is also an object of the present invention to provide precursors for electrode active materials, which precursors can be easily produced. [Means for solving the problem]
[0006] Thus, a method as defined at the outset has been found, also called "method of the invention" or "method according to the (present) invention". The method of the invention comprises at least three steps, also called in the following respectively as step (a), step (b) and step (c), or even more simply as (a), (b) and (c). The method of the invention may comprise further (optional) steps. Steps (a) to (c) are explained in more detail below. The method of the invention gives highly spherical precursors with narrow particle size distribution and with favorably oriented primary particles leading to a high density of the precursors produced by the method of the invention. [Brief description of the drawings]
[0007] [Figure 1] Figure 1 shows a cross-sectional micrograph of P-CAM.1. The core and shell are composed of essentially radially oriented primary particles, although there can also be a layer of non-oriented primary particles between the core and shell. [Diagram 2] Figure 2 shows a cross-sectional micrograph of CP-CAM.2. The core of CP-CAM.2 is formed by non-oriented primary particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The method of the present invention is a method for producing a particulate (oxy)hydroxide or a particulate (oxy)hydroxide of TM, which therefore functions as a precursor of an electrode active material and is therefore also called a precursor.
[0009] In one embodiment of the invention, the resulting precursor is composed of secondary particles which are aggregates of primary particles.
[0010] In one embodiment of the present invention, the specific surface area (BET) of the resulting precursor is 2 to 70 m 2 / g, determined for example by nitrogen adsorption in accordance with DIN-ISO 9277:2003-05. The outgassing temperature is 120°C.
[0011] The precursor is an (oxy)hydroxide of TM, where TM comprises Ni, Co and at least one metal selected from Mn and Al, and optionally at least one further metal selected from Ti, Zr, Mo, W, Mg and Nb.
[0012] In one embodiment of the invention, TM is a combination of metals according to general formula (I): (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.95, preferably 0.8 to 0.94, b is in the range of 0.025 to 0.2, preferably 0.025 to 0.15; c is in the range of 0 to 0.2, preferably 0 to 0.15; d is in the range of 0 to 0.1, M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1 and b+c>0 Or, M comprises Al and d>0.
[0013] In another embodiment of the present invention, TM corresponds to the general formula (II): (Ni a Co b Mn c ) 1-d M d (II) (In the formula, a is in the range of 0.25 to 0.4, b is in the range of 0 to 0.2, c is in the range of 0.6 to 0.75, d is in the range of 0 to 0.1, M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1).
[0014] In either case, the TM may contain, as impurities, trace amounts of further metal ions, e.g., trace amounts of ubiquitous metals such as sodium, iron, calcium or zinc, but such trace amounts are not taken into account in the context of this invention, trace amounts in this context meaning amounts of 0.05 mol % or less relative to the total metal content of the TM.
[0015] The precursor is a particulate material. In one embodiment of the present invention, the precursor has an average particle size D50 in the range of 3 to 20 μm, preferably 4 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles are composed of primary particles, in particular they are aggregates of primary particles, and the above particle size refers to the particle size of the secondary particles.
[0016] In one embodiment of the invention, the span of the particle size distribution of the precursor is in the range of 0.9 to 2.0, which span is defined as [(D90)-(D10)] / (D50), where the values of (D90), (D50) and (D10) are determined by dynamic light scattering.
[0017] The particulate matter may have an irregular shape, but in a preferred embodiment the particulate matter has a regular shape, for example an ellipsoid or even a sphere. The aspect ratio may range from 1 to 10, preferably from 1 to 3, even more preferably from 1 to 1.5. The aspect ratio is defined as the ratio of width to length, or more specifically the ratio of the particle size in the longest dimension to the particle size in the shortest dimension. A perfectly spherical particle has an aspect ratio of 1.
[0018] Step (a) comprises providing at least one aqueous solution (α) containing a water-soluble salt of Ni, at least one metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta, an aqueous solution (β) containing an alkali metal hydroxide, and optionally an aqueous solution (γ) containing a complexing agent, for example ammonia.
[0019] The term water-soluble salts of cobalt and nickel or manganese, or of metals other than nickel and cobalt and manganese, refers to salts that have a solubility in distilled water at 25° C. of 25 g / l or more, the amount of salt being determined under the omission of water of crystallization and water resulting from aquo complexes. The water-soluble salts of nickel and cobalt and manganese are preferably Ni 2+ and Co 2+ and Mn 2+ Examples of water-soluble salts of nickel and cobalt are sulfates, nitrates, acetates and halides, especially chlorides. Preferred are the nitrates and sulfates, of which the sulfates are more preferred.
[0020] The term "water-soluble compounds of aluminum" refers to compounds such as Al2(SO4)3, Al(NO3)3, KAl(SO4)2, NaAlO2, and NaAl(OH)4. Depending on the choice of the water-soluble compound of aluminum, the pH value of the aqueous solution (α) is in the range of 1-3 or above 13.
[0021] Examples of suitable Mg compounds are MgSO4, Mg(NO3)2, magnesium acetate and MgCl2, with MgSO4 being preferred.
[0022] Examples of suitable compounds of Ti are Ti(SO4)2, TiOSO4, TiO(NO3)2, Ti(NO3)4, with Ti(SO4)2 being preferred. Examples of suitable Zr compounds are zirconium acetate, Zr(SO4)2, ZrOSO4, ZrO(NO3)2, Zr(NO3)4, with Zr(SO4)2 being preferred.
[0023] Examples of suitable Nb compounds are (NH4)Nb(C2O4)3 and (NH4)NbO(C2O4)2. Examples of suitable Mo compounds are MoO3, Na2MoO4 and (NH4)2MoO4.
[0024] Examples of suitable W compounds are WO3, WO3·H2O, Na2WO4, ammonium tungstate, and tungstic acid.
[0025] Solution (α) may have a pH value in the range of 2 to 5. In embodiments where a higher pH value is desired, ammonia may be added to solution (α). However, it is preferred not to add ammonia to solution (α). If it is intended to provide a solution containing NaAlO2 and NaAl(OH)4, it is preferred to provide at least two aqueous solutions, where one solution contains nickel, at least one of cobalt and manganese, and optionally at least one of Ti, Zr, Mo, W, Mg, Nb and Ta, and another aqueous solution contains NaAlO2 or NaAl(OH)4.
[0026] The concentrations of nickel and other components of the TM can optionally be chosen within wide ranges, with the respective total metal concentrations preferably being chosen to be within the range of 1 to 1.8 moles of metal per kg of solution, more preferably 1.3 to 1.7 moles of metal per kg of solution.
[0027] Furthermore, in step (a), an aqueous solution of an alkali metal hydroxide, hereinafter also referred to as solution (β), is provided. Examples of alkali metal hydroxides are potassium hydroxide and a combination of sodium hydroxide and potassium hydroxide, more preferably sodium hydroxide.
[0028] In one embodiment of the present invention, solution (β) mainly contains alkali metal hydroxides and a certain amount of carbonate, for example 0.1 to 2 mass % based on the amount of each alkali metal hydroxide, which carbonate is either intentionally added or is formed by aging of solution (β) or the respective alkali metal hydroxide.
[0029] The solution (β) has a hydroxide concentration in the range of 0.1 to 12 mol / l, preferably 6 to 10 mol / l.
[0030] The pH value of the solution (β) is preferably greater than or equal to 13, for example 14.5.
[0031] Solution (γ) contains a complexing agent, examples of which are ammonia and organic acids or their alkali or ammonium salts, where the organic acids have at least two functional groups per molecule, at least one of the functional groups being a carboxylate group.
[0032] Examples of organic acids with two identical functional groups are adipic acid, oxalic acid, succinic acid, and glutaric acid. An example of an organic acid with three identical functional groups is citric acid.
[0033] In one embodiment of the invention, the organic acid is selected from malic acid, tartaric acid, citric acid, and glycine.
[0034] In one embodiment of the present invention, the concentration of the complexing agent(s) in solution (γ) is in the range of 1 to 30% by mass. In an embodiment in which the complexing agent is selected from ammonia, the concentration is preferably in the range of 10 to 30% by mass. In an embodiment in which the complexing agent(s) is selected from organic acids, or their alkali or ammonium salts, the organic acids having at least two functional groups per molecule, at least one of the functional groups being a carboxylate group, the concentration of the complexing agent in solution (γ) may be in the range of 0.2 to 10% by mass.
[0035] The more preferred complexing agent is ammonia.
[0036] In steps (b) and (c), solution (α), solution (β) and, if applicable, solution (γ) are combined under hydroxide precipitation. They are combined in at least two stirred tank reactors, each equipped with a solid-liquid separator, through which the mother liquor is removed. The mother liquor contains counterions of the metals of TM and alkali metal ions from the base in solution (β). Examples of solid-liquid separators include clarifiers, such as lamellar clarifiers, filtration devices, such as filter presses, hydrocyclones, and filters, such as at least one candle filter. Using one or more such solid-liquid separators, a slurry having a solids content of 1200 g / l or less is obtained.
[0037] The proportion of mother liquor removed in steps (b) and (c) can range from 200 to 1,200 g / l, preferably from 800 to 1,200 g / l. However, despite the removal of the mother liquor, the slurry remains well stirrable. Step (b) comprises combining solution (α)(s), solution (β) and, where applicable, solution (γ) in a continuous reactor, thereby producing solid particles of hydroxide of TM, said solid particles being slurried.
[0038] In one embodiment of the invention, the particles obtained from step (b) have an average diameter in the range of 2 to 10 μm.
[0039] In step (b), the pH value of the liquid phase of the slurry is in the range of 12.0 to 13.0. The pH value is determined at 23° C. in the liquid phase.
[0040] In one embodiment of the present invention, the average hydraulic residence time of the slurry in step (b) is in the range of 30 minutes to 12 hours, preferably in the range of 1 to 8 hours, more preferably in the range of 2 to 6 hours.
[0041] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 10 to 85°C, preferably at a temperature in the range of 20 to 70°C.
[0042] In one embodiment of the invention, step (b) is carried out at constant pressure, for example at atmospheric pressure, hi another embodiment, step (b) is carried out at elevated pressure, for example up to 50 bar.
[0043] In one embodiment of the present invention, excess mother liquor is removed from the continuous reactor during step (b). The mother liquor contains water and an alkali metal salt. The alkali counterions are counterions of nickel and counterions of metals other than nickel. For example, when nickel sulfate is used in solution (α) and sodium hydroxide is used in solution (β) as the water-soluble salt of nickel, the mother liquor contains sodium sulfate.
[0044] In one embodiment of the invention, the solids content of the slurry transferred to step (c) or storage vessel (see below) ranges from 200 to 1200 g / l. Prior to the start of step (c), the slurry from step (b) is preferably diluted to 2 to 100 g / l, for example with deionized water or mother liquor, in the reactor in which step (c) is carried out. The solids content can be determined by density measurement or ICP (inductively coupled plasma) or Coriolis meter and refers to the slurried particles. Dissolved compounds such as (but not limited to) Na2SO4 are ignored in this context.
[0045] In one embodiment of the invention, step (b), like step (c), is carried out under an inert atmosphere, for example under a noble gas such as nitrogen or argon. Oxygen-depleted air, for example air with 2% by weight or less O2, can be used as well, especially if the TM does not contain manganese. CO2 is not a suitable atmosphere because solution (β) is strongly alkaline.
[0046] In step (c), the slurry from step (b) is transferred to a stirred tank reactor operated continuously or preferably batchwise, where solution (α), solution (β) and, where applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0.
[0047] In step (c), the pH value of the liquid phase of the slurry is in the range of 11.0 to 12.0. The pH value is determined at 23°C.
[0048] Solution (α), solution (β) and, if applicable, solution (γ) in step (c) are defined as above. They may have the same composition as their counterparts in step (b) or may be different, but within the framework of the above definition, for example, one of them contains nickel and at least one water-soluble salt of cobalt and manganese. In such a case, they are also called solution (α'), solution (β') and, if applicable, solution (γ'), respectively. However, preferably, the composition of solution (α) in steps (b) and (c) is the same.
[0049] Even more preferably, the composition of solution (α) and the composition of solution (β) in steps (b) and (c) are identical.
[0050] In one embodiment where step (c) is carried out in a stirred tank reactor operated batchwise, the composition of solution (α) or (α') optionally changes during the course of step (c), e.g. the concentrations of nickel and cobalt or manganese change. In another embodiment of the invention, the composition of solution (α) or (α') optionally remains constant.
[0051] In one embodiment of the present invention, the duration of step (c) is in the range of 30 minutes to 80 hours, preferably in the range of 10 to 70 hours, more preferably in the range of 15 to 60 hours.
[0052] In one embodiment of the present invention, step (c) is carried out at a temperature in the range of 10 to 85°C, preferably at a temperature in the range of 20 to 60°C.
[0053] In one embodiment of the invention, step (c) is carried out at constant pressure, for example at atmospheric pressure, hi another embodiment, step (b) is carried out at elevated pressure, for example up to 50 bar.
[0054] In one embodiment of the invention, the process of the invention is carried out in a cascade of at least two stirred tank reactors, a first of which is equipped with an overflow system through which slurry is removed from the first stirred tank reactor and transferred directly or indirectly to a second stirred tank reactor.
[0055] In a preferred embodiment, the slurry is removed from the continuous stirred tank reactor in which step (b) is carried out and transferred to a stirred storage vessel where it is stored under stirring for a period of time between 15 minutes and 24 hours, preferably between 30 minutes and 10 hours, before being transferred to a second stirred tank reactor. This operation is also called the storage step. During the course of the storage step, neither solution (α), nor solution (β), nor solution (γ) is added. The storage is preferably carried out under inert gas (see above).
[0056] In one embodiment of the present invention, the temperature during the storage step is in the range of 20 to 70°C, preferably 30 to 60°C.
[0057] In one embodiment of the present invention, the pH value of the slurry in the storage vessel is in the range of 10.0 to 13.0, preferably 12.0 to 12.5, determined at 23°C.
[0058] In one embodiment of the invention, at the same time, in the range of 5-30% by volume, preferably 10-20% by volume, of the slurry is in the storage vessel and 70-95% by volume, preferably 80-90% by volume, of the slurry is in the tank reactor where steps (b) and (c) are carried out. In this context, the amount of slurry placed in the piping or related parts is ignored.
[0059] In one embodiment of the invention, the slurry in the storage vessel is stirred from time to time, for example with an average energy input of 0.2-1 W / l, which is useful to avoid settling of the solids in the slurry.
[0060] By carrying out the method of the present invention, solid particles of hydroxide or oxyhydroxide are produced and the solid particles are slurried to obtain a slurry. Preferably, the slurry has a solid content in the range of 200 to 1,200 g / l.
[0061] In one embodiment of the invention, a clarifier or at least one candle filter is used to remove the mother liquor. Such candle filter(s) is / are connected to the stirred vessel in such a way that the mother liquor can be easily removed, but the solids are retained within the stirred vessel.
[0062] Step (c) may be followed by further steps, such as a work-up step (d), for example the removal of the (oxy)hydroxide particles by a solid-liquid separation method, such as filtration.
[0063] In such step (d), the particles from step (c) are separated from the liquid phase by a solid-liquid separation method, preferably filtration or centrifugation. The liquid phase is also called mother liquor. Filtration can be carried out, for example, with a belt filter or a filter press.
[0064] The filter cake is preferably washed, for example with water or an alkali metal hydroxide or alkali metal carbonate solution, to remove the mother liquor. Filtration is accomplished by suction or pressure.
[0065] Step (d) may be carried out at a temperature at which water is in a liquid state, for example, from 5 to 95°C, preferably from 20 to 60°C.
[0066] By carrying out step (d) a solid material is obtained which is a particulate (oxy)hydroxide or oxide of TM. The material usually has a high moisture content, for example 1-30% by weight, and can be dried, for example in air at a temperature in the range 80-150°C or under reduced pressure ("vacuum") to a moisture content in the range 100-5,000 ppm (ppm being ppm by weight). The moisture content can be determined by drying in vacuum at a temperature of 100°C until no change in mass occurs. The moisture content may be determined by Karl Fischer titration. Following step (d) or drying, the particulate (oxy)hydroxide or oxide of TM may be subjected to step (e), which involves heat treatment of the solids from step (d) in a rotary kiln or flash calciner.
[0067] In one embodiment of step (e), the moist solid material is introduced into the rotary kiln by a chute or vibrating chute, a spiral conveyor or a screw conveyor, preferably a screw conveyor having a single screw or multiple screws.
[0068] A further aspect of the invention relates to a particulate (oxy)hydroxide of TM, hereinafter also called the (oxy)hydroxide of the invention or the precursor of the invention, which is advantageously prepared according to the method of the invention.
[0069] In the (oxy)hydroxides of the invention, TM means a combination of nickel and at least one metal selected from cobalt and manganese, said (oxy)hydroxides of the invention have an average particle size (d50) in the range of 3 to 20 μm, preferably 4 to 16 μm, and have a core-shell structure, where both the core and the shell exhibit an essentially radial arrangement of the primary particles of the platelets, the core and the shell being separated by a porous layer containing randomly arranged primary particles.
[0070] The porous layer can be detected by scanning electron microscopy ("SEM") or transmission electron microscopy ("TEM"). In the porous layer, usually only a small amount of voids are detected. Preferably, the porous layer between the core and the shell has an average thickness in the range of 0.1 to 1.0 μm.
[0071] The fraction of radially arranged primary particles can be determined, for example, by SEM (scanning electron microscopy) of cross-sections of at least five secondary particles.
[0072] "Essentially radially disposed" does not require a perfect radial orientation, but includes a maximum deviation of 5 degrees from a perfect radial orientation upon SEM analysis.
[0073] Furthermore, at least 70% by volume of the secondary particles are filled with radially arranged primary particles, preferably only a small inner portion of the volume of the particles, e.g. up to 30% by volume, preferably up to 20% by volume, is filled with non-radially arranged primary particles, e.g. with random orientation.
[0074] In the porous layer, the percentage of voids is preferably more than 10%, as calculated from five representative particles selected by SEM.
[0075] In one embodiment of the present invention, the (oxy)hydroxide of the present invention has a particle size distribution with a span [(d90)-(d10)] / (d50) in the range of 0.2 to 0.6. The diameters (D10), (D50) and (D90) can be determined by dynamic light scattering.
[0076] In one embodiment of the present invention, TM in the (oxy)hydroxide of the present invention is a combination of metals according to general formula (I), (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.95, preferably 0.8 to 0.94, b is in the range of 0.025 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1, M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1).
[0077] In another embodiment of the present invention, TM in the (oxy)hydroxide of the present invention is a combination of metals according to general formula (II), (Ni a Co b Mn c ) 1-d M d (II) (In the formula, a is in the range of 0.25 to 0.4, b is in the range of 0 to 0.2, c is in the range of 0.6 to 0.75, d is in the range of 0 to 0.1, M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb, and Ta; a+b+c=1).
[0078] The (oxy)hydroxide of the present invention is preferably obtained according to the method of the present invention. The (oxy)hydroxide of the present invention is an excellent starting material for a cathode active material suitable for the manufacture of a battery having a high volumetric energy density and good cycling stability. Such a cathode active material is prepared by mixing with a lithium source, e.g. LiOH or Li2O2 or Li2CO3, followed by calcination at a temperature in the range of e.g. 600-1000°C. In particular, in an embodiment in which the TM of the (oxy)hydroxide of the present invention corresponds to formula (I), the calcination is preferably carried out in an atmosphere of oxygen or oxygen-enriched air, e.g. having at least 60% by volume of oxygen, preferably 80% by volume of oxygen, more preferably at least 90% by volume of oxygen. In an embodiment in which the TM of the (oxy)hydroxide of the present invention corresponds to formula (II), the calcination can be carried out in an air atmosphere.
[0079] Examples of equipment suitable for calcination are rotary kilns, roller hearth kilns, and pusher kilns.
[0080] Calcination as described above preserves the essentially radial orientation of the primary particles (eg, at least 80%, preferably at least 90%), resulting in a cathode active material with excellent capacity retention.
[0081] The invention is further illustrated by examples and figures. EXAMPLES
[0082] Brief Description of the Drawings, Figure 1: Schematic setup. Reactor A of step (b) is a stirred tank reactor equipped with a clarifier for removal of mother liquor. The bottom valve is not shown.
[0083] The aging tank is in the center. Reactor B for carrying out step (c) is on the right and is equipped with a clarifier.
[0084] I. Synthesis of Precursors Summary: The following setup was used: A 3.2 liter stirred tank reactor ("first precipitation reactor" or "Reactor A") equipped with baffles, a 0.06 m diameter cross-arm agitator, and a glass cylindrical clarifier through which mother liquor could be removed from Reactor A. Reactor A was further equipped with a bottom valve.
[0085] Reactor A is equipped with an overflow system leading to a stirred aging tank (volume 25 liters), which is connected to a second settling tank (or "Reactor B"), a stirred tank reactor of volume 3.2 liters equipped with baffles, a 0.06 m diameter cross-arm agitator, and a glass cylindrical clarifier.
[0086] Both clarifiers are equipped with pumps that allow the reintroduction of the paste-like residue, with a very high solids content, from the bottom of the cylindrical glass clarifier into the respective reactors.
[0087] rpm: Revolutions per minute.
[0088] In step (a.1) the following aqueous solution was provided: Solution (α.1): NiSO4, CoSO4, and MnSO4 dissolved in deionized water (molar ratio 91:4.5:4.5, total transition metal concentration 1.65 mol / kg).
[0089] Solution (β.1): 25% by weight NaOH dissolved in deionized water Solution (γ.1): 25% by weight ammonia in deionized water.
[0090] I.1 Synthesis of the precursor P-CAM.1 of the invention Reactor A of the above setup was charged with 1.6 l of deionized water containing 15 g of ammonia and heated to 55° C. Then solution (β.1) was added to a pH value of 12.18 at 23° C. and the stirrer was set at 700 rpm.
[0091] Step (b.1): Solutions (α.1), (β.1) and (γ.1) were then continuously fed into reactor A so that the pH value of the mother liquor measured at 23° C. was 12.2 and the molar ratio of NH3 to the sum of Ni, Co and Mn in reactor A was 0.22. The precipitation was carried out under an atmosphere of N2. The flow rates of each of the solutions were adjusted to meet a hydraulic residence time of 5 hours.
[0092] During the course of step (b.1), particle-free mother liquor was continuously removed from reactor A by a clarifier, while the concentrated slurry was returned to reactor A. The clarifier pump was operated such that less than 10% of the total particle mass was present in the clarifier. The mass flow rate of the removed mother liquor was 65% of the feed mass flow rate. In parallel with the removal of the mother liquor, the produced slurry was continuously discharged from reactor A by free overflow and collected in an ageing tank. With this approach, the solids content of the slurry in reactor A was increased to 395 g / l and remained constant during the continuous operation of step (b.1).
[0093] The resulting slurry with an average particle size (d50) of 4.2 μm was collected in a stirred aging tank. After a residence time of 1 day, a portion of this slurry was transferred to reactor B, which was charged with a solution containing 20 g of ammonia at 55° C. with a pH value of 11.4 measured at 23° C.
[0094] Step (c.1): Then, the injection of solutions (α.1), (β.1) and (γ.1) was started. The flow rates of each of the solutions were adjusted to meet the hydraulic residence time of 5 hours. Over a precipitation time of 21 hours, mother liquor was continuously removed from the slurry, finally obtaining a high solids slurry that was removed from reactor B through the bottom valve.
[0095] The slurry was then separated by filtration, washed with deionized water and solution (β1), and dried at 120 °C for 16 h to obtain precursor P-CAM.1 with a molar composition of Ni:Co:Mn = 91:4.5:4.5, average particle size (d50) = 13.4 μm, and span = 0.42. This precursor showed excellent sphericity with a shape factor of 0.989. Furthermore, SEM analysis of P-CAM.1 shows a core-shell structure with a radial arrangement of platelet-like primary particles in the core and shell, and a porous layer between the core and shell with randomly oriented primary particles.
[0096] I.2 Synthesis of comparative precursor CP-CAM.2 Step (a.2): The same solutions (α.1), (β.1) and (γ.1) as in I.1 were used.
[0097] Step c-(b.2): A 3.2 liter stirred tank reactor similar to reactor A was charged with 1.6 liters of deionized water containing 7 g of ammonia and heated to 55 °C. Then solution (β.1) was added so that the pH value measured at 23 °C was 12.2, and the stirrer was set at 1000 rpm. Then solutions (α.1), (β.1) and (γ.1) were continuously fed into the tank reactor so that the pH value of the mother liquor was 12.2 at 23 °C and the molar ratio of NH3 to the sum of Ni, Co and Mn in the reactor was 0.1. This process was carried out under an inert gas atmosphere. The flow rate of each of the solutions was adjusted to meet a hydraulic residence time of 5 hours.
[0098] The slurry with an average particle size (d50) of 4.1 μm was continuously discharged by free overflow and collected in an aging tank. The solid content of the slurry was 125 g / l.
[0099] After 24 hours, a portion of this slurry was transferred to reactor B, which was charged with a solution containing 20 g of ammonia at 55° C., with a pH value of 11.4 measured at 23° C. This second reactor was also equipped with a mother liquor takeoff, but had no free overflow.
[0100] Step (c.2): Then, the injection of solutions (α.1), (β.1) and (γ.1) was started. The flow rates of each of the solutions were adjusted to meet the hydraulic residence time of 5 hours. Over a precipitation time of 21 hours, mother liquor was continuously removed from the slurry, finally obtaining a high solids slurry that was removed from reactor B through the bottom valve.
[0101] The recovered slurry was then separated by filtration, washed with deionized water and solution (β1), and dried at 120 °C for 16 h to obtain comparative precursor CP-CAM.2 with a molar composition of Ni:Co:Mn = 91:4.5:4.5, average particle size (d50) = 13.2 μm (measured by laser diffraction), and span = 0.45. Compared to P-CAM.1, the sphericity was lower at 0.974. Moreover, only the shell of comparative precursor CP-CAM.2 showed a radial arrangement of platelet-like primary particles, while the core consisted of randomly oriented primary particles.
[0102] II. Preparation of Inventive and Comparative Cathode Materials II.1 Preparation of dehydrated metal oxide precursors 50 g of P-CAM.1 was heated in a Linn oven under flowing air at 450° C. for 2 hours. The metal oxide P-CAM.O.1 had an average particle size (D50) of 13.3 μm and a span of 0.39.
[0103] For comparison, 50 g of CP-CAM.2 was heated in a Linn oven under flowing air for 2 hours at 450° C. The metal oxide CP-CAM.O.2 had an average particle size (D50) of 13.1 μm and a span of 0.42.
[0104] II.2 Firing and post-treatment 30 g of P-CAM.O.1 was mixed with LiOH monohydrate (molar ratio Li / metal=1.02), 133 mg of TiO2, and 122 mg of ZrO2 in a grinder for 15 min. The resulting mixture was loaded into a saggur and transferred to a Linn oven. The temperature was increased to 750°C at 2°C / min under flowing oxygen, then held at 750°C for 8 h, followed by natural cooling under flowing oxygen. The resulting powder was then deagglomerated in a grinder and sieved. The deagglomerated powder had an average particle size (D50) of 13.2 μm, a span of 0.37, and an average shape factor of 0.991.
[0105] 30 g of the powder was then added to 15 ml of deionized water, stirred for 2 minutes, and then immediately filtered through a Buchner funnel to remove the water. The wet filter cake was then dried at 120° C. under reduced pressure and N2 atmosphere for 10 hours.
[0106] The resulting powder was then dry-coated with boric acid by mixing 30 g of the resulting powder, mixing medium, and 30 mg of boric acid in a roller mill at low speed for 40 minutes. The dried powder was loaded into a sagger and heat-treated in a Linn oven. The Linn oven was heated at 300°C under oxygen atmosphere for 2 hours and naturally cooled. CAM.1 of the present invention was obtained.
[0107] The comparative oxide PCAM CP-CAM.O.2 was treated similarly to give C-CAM.2 After deagglomeration, the resulting powder had an average particle size (D50) of 13.0 μm, a span of 0.41, and an average shape factor of 0.973.
[0108] III. Testing of Cathode Active Materials III.1 Cathode fabrication Cathode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 7.5 wt% solution. For electrode preparation, the binder solution (3 wt%), graphite (SFG6L, 2 wt%) and carbon black (Super C65, 1 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), the inventive CAM.1 or C-CAM.2 (94 wt%) was added and the suspension was mixed again to obtain a lump-free slurry. The solid content of the slurry was adjusted to 65%. The slurry was coated on Al foil using a KTF-S roll-to-roll coater (Mathis AG). All electrodes were calendered before use. The thickness of the cathode material was 70 μm, with a concentration of 15 mg / cm. 2 All electrodes were dried at 105 °C for 7 h before assembling into cells.
[0109] III.2 Preparation of electrolyte A base electrolyte composition (EL Base 1) was prepared containing 12.7 wt% LiPF6, 26.2 wt% ethylene carbonate (EC), and 61.1 wt% ethyl methyl carbonate (EMC), based on the total weight of EL Base 1. 2 wt% vinylene carbonate (VC) was added to this base electrolyte (EL Base 2).
[0110] III.3 Coin Cell Manufacturing A coin-shaped half-cell (20 mm in diameter and 3.2 mm in thickness) containing the cathode prepared as described in II.1.1 and lithium metal as working and counter electrodes, respectively, was assembled and sealed in an Ar-filled glove box. The cathode, anode, and separator were further stacked in the order of cathode / / separator / / Li foil to fabricate a half-coin cell. Then, 0.15 mL of EL base 1 described above (III.2) was introduced into the coin cell.
[0111] III.4 Cycle Test The initial performance, C-rate performance and cycle performance were measured as follows: A coin half-cell according to III.3 was tested in the voltage range of 4.3 V to 2.8 V at room temperature. For the initial cycle, the initial lithiation was performed in CC-CV mode, i.e., a constant current (CC) of 0.1 C was applied until 4.3 V was reached, followed by a CV step until the current dropped to 0.01 C. After a rest period of 10 min, reductive lithiation was performed at a constant current of 0.1 C up to 2.8 V. For the C-rate test, the charge and discharge rates were adjusted accordingly. For the cycle test, the constant current was chosen to be 1 C until 100 cycles were reached. The results are summarized in Table 1.
[0112] [Table 1]
[0113]
Claims
1. A method for producing a particulate (oxy)hydroxide of TM, wherein TM represents a combination of nickel and at least one metal selected from Co and Mn, said method comprising the following steps: (a) providing one or more aqueous solutions (α) containing water-soluble salts of Ni, at least one metal selected from Co and Mn, and optionally at least one further metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta, an aqueous solution (β) containing an alkali metal hydroxide, and optionally an aqueous solution (γ) containing a complexing agent; (b) combining solution (α), solution (β), and, where applicable, solution (γ) in a continuous stirred tank reactor at a pH value in the range of 12.0 to 13.0 as determined at 23° C. to produce hydroxide solid particles, said solid particles being slurried; (c) transferring the slurry from step (b) to a stirred tank reactor where solution (α), solution (β), and, where applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0 as determined at 23° C.; Including, The process wherein each stirred tank reactor(s) is equipped with a solid-liquid separation device in which mother liquor is removed from the stirred tank reactor(s).
2. TM is a combination of metals according to general formula (I), (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.95; b is in the range of 0.025 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta; a + b + c = 1) The method of claim 1.
3. TM is a combination of metals according to general formula (II), (Ni a Co b Mr c ) 1-d M d (II) (wherein a is in the range of 0.25 to 0.4; b is in the range of 0 to 0.2; c is in the range of 0.6 to 0.75; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta; The method of claim 1 , wherein a+b+c=1.
4. 4. The process according to any one of claims 1 to 3, carried out in a cascade of at least two stirred tank reactors, a first of which is equipped with an overflow system through which slurry is removed from the first stirred tank reactor and transferred directly or indirectly to a second stirred tank reactor.
5. 5. The process of any one of claims 1 to 4, wherein the slurry is removed from the continuous stirred tank reactor and transferred to a stirred storage vessel where it is stored under agitation for 15 minutes to 24 hours before being transferred to a second stirred tank reactor.
6. The method according to claim 5, wherein the temperature during the storage step is in the range of 20 to 70°C.
7. The method according to claim 5 or 6, wherein the pH value of the slurry in the storage vessel is determined at 23° C. and is in the range of 10.0 to 13.
0.
8. 8. The method according to any one of claims 5 to 7, wherein at the same time, in the range of 5 to 30 vol.% of the slurry is in the storage vessel and 70 to 95 vol.% of the slurry is in the tank reactor in which steps (b) and (c) are carried out.
9. 9. The method according to claim 1, wherein in at least one of steps (b) and (c), coaxial nozzles are used for the addition of solution (α) and solution (β) or solution (α) and solution (γ).
10. 10. The process according to any one of claims 1 to 9, wherein in at least one of steps (b) and (c), a clarifier or at least one candle filter is used to remove the mother liquor.
11. 1. A particulate (oxy)hydroxide of TM, where TM refers to a combination of nickel and at least one metal selected from cobalt and manganese, said particulate (oxy)hydroxide having an average particle size (d50) in the range of 3 to 20 μm and a core-shell structure, both the core and the shell exhibiting an essentially radial arrangement of the primary particles of the platelets, the core and the shell being separated by a porous layer containing randomly arranged primary particles.
12. 12. A particulate (oxy)hydroxide according to claim 11, having a particle size distribution with a span [(d90)-(d10)] / (d50) in the range of 0.2 to 0.
6.
13. TM is a combination of metals according to general formula (I), (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.95; b is in the range of 0.025 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta; The particulate (oxy)hydroxide according to claim 11 or 12, wherein a+b+c=1.
14. TM is a combination of metals according to general formula (II), (Ni a Co b Mr c ) 1-d M d (II) (wherein a is in the range of 0.25 to 0.4; b is in the range of 0 to 0.2; c is in the range of 0.6 to 0.75; d is in the range of 0 to 0.1; M is selected from Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta; 14. The particulate (oxy)hydroxide according to any one of claims 11 to 13, wherein a+b+c=1.
15. A particulate (oxy)hydroxide according to any one of claims 11 to 14, wherein the porous layer between the core and the shell has an average thickness in the range of 0.1 to 1.0 μm.